Organizational Assessment of a MSME in the gastronomy sector: Case Study with Business Self-Diagnosis Tool - Grillo Torres, Camilo Mauricio; Vega, Catalina Rocío; Gómez Espinosa, Claudia Patricia; Mosquera Laverde, William Eduardo (Cooperativismo & Desarrollo, 2024)
Organizational self-diagnosis is defined as a complete evaluation of the areas that affect the achievement of goals within an organization; a case study is applied to a SME in the gastronomic sector. The study aims to verify and explain the self-diagnosis activities carried out within the company as a unit of analysis. To do so, a qualitative descriptive approach is used to establish a self-diagnosis through an office automation tool to induce adequate administrative and operational management. During the development of the study, strengths were identified in the quality of the company's processes. Still, deficiencies were also found in the areas of marketing and finance, mainly due to the weakness in the strategic actions of marketing planning, as well as poor financial planning and failures in the analysis and control in this area. The study concludes that it is necessary to strengthen the company's marketing and financial management to achieve qualified management of the organization.
Keywords: Organizational self-diagnosis; small business; Office automation; Organizational management; Strategy